The clinical and genetic profiles of spinal muscular atrophy with respiratory distress type 1 and identification of a novel mutation in IGHMBP2 in China - Wang, Yanjun; Yang, Ya; Wang, Jingjing; Han, Qian; Zhai, Nana; Xiao, Shufang (Frontiers in Genetics, 2025)
BackgroundSpinal muscular atrophy with respiratory distress type 1 (SMARD1, OMIM #604320) is a rare autosomal recessive hereditary degenerative motor neuron disease caused by mutations in IGHMBP2. There is a lack of data from China. This study investigated the clinical characteristics and genetic roots of SMARD1 patients.MethodsRoutine detailed clinical assessments, laboratory examinations, and imaging assays were performed. Genetic variations in the families were investigated using whole-exome sequencing and Sanger sequencing, and then bioinformatic analyses were performed on the identified variant.ResultsHere, we describe three female patients with SMARD1 from three unrelated families carrying compound heterozygous mutations in the IGHMBP2 gene, which were inherited from both parents. Six mutations including a novel one (c.716T>C/p.L239P) were identified. Multiple lines of bioinformatic evidence suggested that the novel mutation was a likely detrimental variant. The c.1060G>A/p.G354S mutation was detected in both P1 and P3 and may be a hotspot in the Chinese population. Clinical presentations included delay in development, respiratory failure, hypotonia, distal limb muscle weakness, and diaphragm eventration or paralysis. Additionally, the variants identified in this study were compiled from relevant literature to analyze disease etiology, finding a distinctive distribution of genotypes across the severity of disease manifestations.ConclusionThis study broadened the knowledge on the genetic profile of SMARD1, improved pediatricians’ awareness of early identification and diagnosis, and offers useful data for patient clinical management.